rd-rskr - Språkbanken Text (University of Gothenburg, 2024)
Skrivelser från riksdagen till regeringen
Riksdagens öppna data: Riksdagsskrivelse
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik